High frequency of genomic deletions—and a duplication—in the LIS1 gene in lissencephaly: implications for molecular diagnosis. Issue 6 (19th February 2008) - Mei, D; Lewis, R; Parrini, E; Lazarou, L P; Marini, C; Pilz, D T; Guerrini, R
Abstract : Background: LIS1 is the main gene causing classical (isolated) lissencephaly predominating in the posterior brain regions (p>a). However, about 40% of patients with this malformation pattern show no abnormality after fluorescence in situ hybridisation (FISH) analysis of the 17p13.3 region and LIS1 sequencing. To investigate whether alternative gene(s) or genomic deletions/duplications of LIS1 may account for the high percentage of individuals who show no abnormalities on FISH and sequencing, we performed multiplex ligation dependent probe amplification assay (MLPA) in a series of patients. Methods: We initially performed DNA sequencing in 45 patients with isolated lissencephaly with a p>a gradient, in whom FISH had revealed normal results. We subsequently performed MLPA in those who were mutation negative, and long range polymerase chain reaction (PCR) to characterise the breakpoint regions in patients in whom the deletions were small enough. Results: We found LIS1 mutations in 44% of patients (20/45) of the whole sample and small genomic deletions/duplications in 76% of the remaining (19/25). Deletions were much more frequent than duplications (18 vs 1). Overall, small genomic deletions/duplications represented 49% (19/39) of all LIS1 alterations and brought to 87% (39/45) the number of patients in whom any involvement of LIS1 could be demonstrated. Breakpoint characterisation, performed in 5 patients, suggests that Alu mediated recombination is a major molecular mechanism underlying LIS1 deletions. Conclusions: LIS1 is highly specific for isolated p>a lissencephaly. The high frequency of genomic deletions/duplications of LIS1 is in keeping with the over representation of Alu elements in the 17p13.3 region. MLPA has a high diagnostic yield and should be used as first line molecular diagnosis for p>a lissencephaly.